The Influence of Parenting Styles on Sexual Behavior and Early Marriage Incidence in Gedog Wetan Village - Wardani, Riza Kusuma; Alfitri, Rosyidah (Jurnal EduHealth, 2025)
There are various parenting patterns carried out by parents. This study aims to identify the Relationship between Parenting Patterns and Sexual Behavior and Early Marriage Incidents in Gedog Wetan Village. This study design is cross-sectional with a sample of 38 respondents in Gedog Wetan, Turen District, Malang Regency with a Purposive sampling technique according to the inclusion criteria. The results of the analysis using Chi Square Analysis using a significance level of α = 5%. The results of the analysis obtained the results of ρ <0.05 (0.000) on sexual behavior and (0.014) on the incidence of early marriage, this shows a significant relationship between Parenting Patterns on Sexual Behavior and Early Marriage Incidents in Gedog Wetan Village. The conclusion is that parents must provide good parenting in a democratic way so that children are better able to understand the impact of sexual behavior and the dangers of early marriage.